"Are You Really Sad?" Infants Show Selectivity in Their Behaviors Toward an Unconventional Emoter. (15th February 2018) - Chiarella, Sabrina S.; Poulin‐Dubois, Diane
Abstract : We examined whether 18‐month‐olds understand how the emotional valence of people's experiences predicts their subsequent emotional reactions, as well as how their behaviors are influenced by the reliability of the emoter. Infants watched a person express sadness after receiving an object that was either inappropriate (conventional emoter) or appropriate (unconventional emoter) to perform an action. Then, infants' imitation, social referencing, and prosocial behaviors (helping) were examined when interacting with the person. Results showed that during the exposure phase, the unconventional group showed visual search patterns suggesting hypothesis testing and expressed less concern toward the person than the conventional group. In the social referencing task, the conventional group preferred to search for the target of a positive expression as opposed to the disgust object. In contrast, the unconventional group was more likely to trust the person's negative expression. As expected, no differences were found between the groups on the instrumental helping tasks. However, during the empathic helping tasks, the conventional group needed fewer prompts to help than the unconventional group. These findings provide the first evidence that the congruence between a person's emotional responses and her experiences impacts 18‐month‐olds' subsequent behaviors toward that person.